New methods for elaborating distributed layouts aimed at minimizing the distribution degree to a satisfactory computational time - Shih, Yung Chin; Gonçalves Filho, Eduardo Vila (Revista Gestão da Produção Operações e Sistemas, 2008)
Maximally distributed layout has exceptional operational performance to process parts (considering processing flexibility or not) in comparison to other types of distributed layouts due to the fact of good machine distribution. Nevertheless, most size of it (and its distribution degree) demands huge computational time when done the traditional way (genetic algorithm). Randomly distributed layout requires less computational effort and it is more efficient than partially and processed layouts since its results are quite inferior to the maximally distributed layout. The main goal of this paper is to present new methodologies for elaborating large distributed layouts to satisfy operational performance in a low computational time. Computational results are presented and compared with each other by varying the size of layouts and types of machines to illustrate the effectiveness of presented methods. Key-words: Distributed layouts; Distribution degree; CPU time.